Effect of crossbreeding and reproduction rate on sensory, physical and chemical quality of lamb and mutton - Schmidt, Dewcille (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2002.